(untitled) (LACCEI, 2024)
The present investigation allowed us to describe the problem that can be seen along the entire Peruvian coast, and specifically, the coast of the La Libertad region, by determining the sanitary quality of the spas in this area using the database provided. by the Healthy Summer program of the Peruvian State Health Sector. A comparative database was used as a tool for the collection, organization and analysis of information, to later be reflected in tables where the criteria of microbiological quality, cleaning quality and presence of hygienic services are detailed, and their subsequent classification in the years 2018 and 2019 In addition, guidelines for environmental management focused on the recovery of spas are formulated. Obtaining as a result that the classification of the spas on the coast of La Libertad is Unhealthy during the years 2018 and 2019, and its approach to guidelines based on activities related to the recovery of the sanitary quality of the spas and the involvement of the users of these for their preservation.